PREDICTORS OF AUDIT QUALITY: AN EMPIRICAL MODEL - William Rudy Soegiharto; Liana Rahardja; Kaswandi Zainal; Wenny Chandra Mandagie (STIE-JIC, 2020)
This study aims to determine the relationship of auditor’s independency, work experience, professional competence and audit accountability on audit quality through a survey conducted in five branches of the Public Accountant Firm Doli, Bambang, Sulistiyanto, Dadang & Ali (CPA FIRM DBSDA), based in Bandung, Malang, Central Jakarta, West Jakarta and South Jakarta. The population is permanent employees who have worked for at least one year in five DBSDA CPA FIRM branches and have completed a Bachelor of Education. The research sample consisted of 38 employees who responded to the distributed questionnaire. The results showed that independence, work experience, professional competence and audit accountability have a positive influence on audit quality. Through the partial testing, we find that auditors’ independency, work experience, professional competency, and accountability have a positive effect on audit quality. The practical implications of the results of the study are: (1) audit work is to be carried out by experienced auditors who have adequate knowledge, (2) senior auditors need to supervise junior auditors in conducting audits and examine work performed by junior auditors, and (3) auditors need to maintain auditor independence to ensure that auditor independence is not influenced by the client.